WORK PRODUCTIVITY DETERMINANTS: THE EFFECTS OF WAGES AND OCCUPATIONAL SAFETY AT PT MUTIARA SAWIT SELUMA - Ayati Mariam Nurlima Putri; Sri Ekowati (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to determine the effect of wages and occupational safety on the work productivity of field workers at pt mutiara sawit seluma. this type of research is a quantitative descriptive study. the population of this study is field workers at pt mutiara sawit seluma as the object of research with a total sampling technique. the data collection technique used is a questionnaire. while the data analysis technique uses descriptive analysis, inferential analysis using spss, multiple linear regression analysis, and coefficient of determination (R2) analysis. the results of this study indicate that wages have a positive effect on the work productivity of field workers at PT. Mutiara Sawit Seluma. this means that the higher and more appropriate the wages received, the higher the work productivity of field workers. Occupational safety has a positive effect on the work productivity of field workers at pt mutiara sawit seluma. the better the implementation of work safety, the higher the work productivity produced. wages and occupational safety simultaneously or together have a positive and significant effect on the work productivity of field workers at pt mutiara sawit seluma, thus indicating that both independent variables have an important role in increasing the work productivity of field workers.